Physical models can provide superior learning opportunities beyond the benefits of active engagements. Issue 5 (3rd October 2018) - Newman, Dina L.; Stefkovich, Megan; Clasen, Catherine; Franzen, Margaret A.; Wright, L. Kate
Abstract: The essence of molecular biology education lies in understanding of gene expression, with subtopics including the central dogma processes, such as transcription and translation. While these concepts are core to the discipline, they are also notoriously difficult for students to learn, probably because they cannot be directly observed. While nearly all active learning strategies have been shown to improve learning compared with passive lectures, little has been done to compare different types of active learning. We hypothesized that physical models of central dogma processes would be especially helpful for learning, because they provide a resource that students can see, touch, and manipulate while trying to build their knowledge. For students enrolled in an entirely active‐learning‐based Cell & Molecular Biology course, we examined whether model‐based activities were more effective than non‐model based activities. To test their understanding at the beginning and end of the semester, we employed the multiple‐select Central Dogma Concept Inventory (CDCI). Each student acted as their own control, as all students engaged in all lessons yet some questions related to model‐based activities and some related to clicker questions, group problem‐solving, and other non‐model‐based activities. While all students demonstrated learning gains on both types of question, they showed much higher learning gains on model‐based questions. Examining their selected answers in detail showed that while higher performing students were prompted to refine their already‐good mental models to be even better, lower performing students were able to construct new knowledge that was much more consistent with an expert's understanding. © 2018 The Authors. Biochemistry and Molecular Biology Education published by Wiley Periodicals, Inc. on behalf of International Union of Biochemistry and Molecular Biology., 46(5):435–444, 2018.